The diffuse radio emission around NGC 5580 and NGC 5588 - De Gasperin, F.; Intema, Hubertus; Williams, W.; Brüggen, M.; Murgia, M.; Beck, R.; Bonafede, A. (Oxford University Press, 2014)
The galaxy pair NGC 5580 and NGC 5588 is part of a loose group of galaxies. They are surrounded by steep-spectrum, extended radio emission which was previously suggested to be a down-scaled example of Mpc-size radio haloes present in galaxies clusters. We present a multifrequency study of the radio emission aimed to clarify its nature. The source has been observed with the Giant Metrewave Radio Telescope at 235, 325 and 610 MHz and the images obtained were combined with archival data to cover the frequency range 150-1400 MHz. The new observations revealed the presence of a second, fainter lobe on the south-east of NGC 5580. The spectral index study of the source shows a flattening of the spectrum (which implies a younger particle population) close to the two galaxies. We argue that the extended radio emission is the remnant of a past activity cycle of the active galactic nucleus present in NGC 5580 and therefore a notable example of a dying radio galaxy located outside dense environments. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.